APLIKASI PERANGKAT LUNAK UNTUK PERENCANAAN PENGELASAN PADA MATERIAL BAJA - . Mulyadi; Fentje Abdul Rauf; Rudy Poeng (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2015)
The development of software in Welding Strength Design have fulfill the demand of quick account and efficiency that could manage and maximize resources. This research aim to get welding strength from several loading systems in steel material using software â€œSmalltalkâ€ The result of the simulation of welding strength design for butt joint, normal tension 34,286 N/mm2 with seam welding strength Fe 390. For lap joint, normal tension 44,63 N/mm2 with seam welding strength Fe 490. At T joint for ring surface, bending strength 64,646 N/mm2 withÂ seam welding strength Fe 590. At T joint for square surface, bending strength 79,502 N/mm2 withÂ seam welding strength Fe 690. Keyword : Smalltalk Software, Welding Strength Design, Welding Joint.